Sustainability of Childhood Obesity Interventions: A Systematic Review - Mok, W.K.H.; Sharif, R.; Poh, B.K.; Wee, L.H.; Reilly, J.J.; Ruzita, A.T. (Pakistan Journal of Nutrition, 2019)
Background and Objective: Childhood obesity is a global epidemic. While childhood obesity intervention programmes have been developed and implemented, few studies have investigated the sustainability of these programmes. This systematic review explored the sustainability of childhood obesity interventions at the individual, interpersonal, organizational, community and public policy levels of the Socio-ecological Model (SEM). Materials and Methods: A keyword search was conducted using the online databases EBSCO, PubMed and Science Direct. The inclusion criteria were primary research, long-term childhood obesity interventions (at least 12 months) with a follow-up of at least 6 months after the end of the intervention, overweight or obesity interventions implemented from 2007 until June 2018 and English as the reporting language. Results: These systematic searches found 1953 studies but only eight met the inclusion criteria. Factors such as programme champion, system/policy, workforce, community capacity, engagement/relationship building, adaptation/adoption, evaluation and feedback, training and education, collaboration and partnership as well as ongoing support contributed to the sustainability of the programme. Conclusion: It is important that future research assesses the sustainability of childhood obesity interventions, particularly at the public policy level. Attention should be given to enhancing sustainability in future intervention studies.